Extension of the registration possibilities and determination of the positioning precision of a multi-scale fringe projection system - Metzner, Sebastian; Hausotte, Tino (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
For providing holistic and complete dataset of sheet bulk metal-formed parts, an optical detection with a fringe projection system is useful. By combining several sensors with varying measuring ranges, the workpiece is captured with adapted spatial resolution depending on the forming zone and geometric requirements. The sensors are registered by a two-dimensional point calibration and registration process. The registration process has already been shown in.1 In this article, the calibration procedure is transferred to the measurement setup with three fringe projection sensors with different measurement resolution. A calibration plate with dot patterns is applied to the positioning unit, which is a high precision hexapod in this set-up. This extended calibration plate allows a continuous control of the registration quality as the sensors are able to capture the calibration plate at any time. For determining the positioning accuracy of the hexapod, a procedure following the DIN EN ISO 10360-3 procedure with three spheres mounted on the hexapod was investigated. Therefore the hexapod was fixed at a coordinate measuring machine Zeiss UPMC 1200 and moved in all 6 degrees of freedom. After each movement, the spheres were measured with a probe, which allows the absolute position precision to be calculated. Comparison of the measurements with the specified translation and rotation movement of the hexapod show a positioning precision of less than 10 μm in the positioning directions x and y.
CRIS-Team Scopus Importer:2020-06-09
Keywords: coordinate measurement; hexapod; multi-scale multisensor measurement system; position precision